An Analysis of Writing Materials Students - Maulana, Achmad (Institut Agama ISlam Negeri Palangka Raya, 2022)
Textbooks have become necessary learning media. It is very important to help teachers be more careful in choosing appropriate books for students. This article was created to determine whether in English book